2022
DOI: 10.1097/ta.0000000000003532
|View full text |Cite
|
Sign up to set email alerts
|

Urine leaks in children sustaining blunt renal trauma

Abstract: BACKGROUND:Few consensus statements exist to guide the timely diagnosis and management of urine leaks in children sustaining blunt renal trauma (BRT). The aims of this study were to characterize kidney injuries among children who sustain BRT, evaluate risk factors for urine leaks, and describe the negative impact of urinoma on patient outcomes and resource consumption. METHODS:A retrospective review was performed of 347 patients, younger than 19 years, who presented with BRT to a single American College of Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the setting of devitalized tissue, partial or total nephrectomy is indicated depending on the extent of the damage, ensuring a watertight closure of the collecting system via an omental pedicle flap or renal fat bolster if a partial nephrectomy is performed [ 96 ]. Urine leaks secondary to renal injury are overall uncommon [ 97 ]; only half require some sort of intervention, which is most commonly stent placement, but the presence of a urine leak is a risk factor for requiring surgical intervention and is associated with increased morbidity [ 97 , 98 ]. Renal artery occlusion is another rare complication of renal trauma, and while data are overall limited, there have been reports of successful management with endovascular intervention [ 99 , 100 ].…”
Section: Nonoperative and Operative Managementmentioning
confidence: 99%
“…In the setting of devitalized tissue, partial or total nephrectomy is indicated depending on the extent of the damage, ensuring a watertight closure of the collecting system via an omental pedicle flap or renal fat bolster if a partial nephrectomy is performed [ 96 ]. Urine leaks secondary to renal injury are overall uncommon [ 97 ]; only half require some sort of intervention, which is most commonly stent placement, but the presence of a urine leak is a risk factor for requiring surgical intervention and is associated with increased morbidity [ 97 , 98 ]. Renal artery occlusion is another rare complication of renal trauma, and while data are overall limited, there have been reports of successful management with endovascular intervention [ 99 , 100 ].…”
Section: Nonoperative and Operative Managementmentioning
confidence: 99%
“…Moreover, the average annual number of pediatric renal injuries more than doubled from P1 to P2 accompanied by an increase in renal injury severity which is likely an effect of the maturation of the trauma system with adherence to triage and transfer criteria implemented in 2010 as described in a previous publication from our institution. 17 Isolated blunt renal trauma is rarer and often presumed to represent a minor injury leading potentially to less timely evaluation as suggested by Ghani et al 1 They found that this group of patients had a higher risk of urine leaks and suspected that these injuries result from greater focal energy transfer (eg, sports-related injury) than multisystem scenarios in which the energy transfer is more diffuse (eg, motor vehicle crash). These speculations are supported by our observations that isolated renal injury was more common in high-grade compared with low-grade injury (table 5).…”
Section: Open Accessmentioning
confidence: 99%
“…1 5 To diagnose urine leaks in a timely fashion, routine on-arrival delayed CT in children with grade 3 injury and above has been recommended. 1 Such a strategy will reduce the need for repeat imaging and excess radiation. 5 Although many of these urine leaks heal spontaneously, kidney interventions and procedures are more common in this category of patients compared with those without leaks.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations